“El modelo de gestión administrativa del hospital oncológico Solca Chimborazo y su incidencia en la toma de decisiones periodo 2015” - Delgado Rodríguez, Solanda Katerine (2017)
The present investigation was carried out in the Hospital Cancer SOLCA Chimborazo being a hospital that provides services oriented to people with catastrophic diseases in this case (cancer). The problem of this hospital has been to determine the efficiency of administrative management since, being a non-profit, but public service company has had to face challenges that have been determinant in the service provided by this unit. Although the administrative management of a hospital does not make much difference with respect to the administration of other types of companies, in the case of SOLCA the challenge is greater since in spite of the limitations with respect to the administrative management that owns this one Unit the executive director has had to face different challenges is why I study the ADMINISTRATIVE MANAGEMENT MODEL OF ONCHOLOGICAL HOSPITAL SOLCA CHIMBORAZO AND ITS INCIDENCE IN THE DECISION MAKING PERIOD 2015 this research is distributed as follows: CHAPTER I.- Through the institutional diagnosis of the SOLCA Chimborazo Oncology Unit I established the origin and creation of the same, its organizational culture, the functional organic structure, as well as the financial structure. It was evident the administrative management of this hospital and the hierarchical order of this hospital. CHAPTER II.- I make reference to the Theoretical Conceptual Framework, in which it is described in detail each of its items, such as: Background, Theoretical Foundation, Structure, Normative. CHAPTER III.- This part of the research describes the methodology used in this research field project and application, as well as the hypothetical deductive method. In addition, interviews were conducted for the development of the same. Finally, the research concludes with the most relevant aspects that have been detected through research in the incidence of administrative management in making appropriate, timely and effective decisions in the Oncology Unit SOLCA - Chimborazo.